Assessment of Solidago×niederederi Origin Based on the Accumulation of Phenolic Compounds in Plant Raw Materials. Issue 3 (4th March 2018) - Radušienė, Jolita; Marksa, Mindaugas; Karpavičienė, Birutė
Abstract: This study provides the first phytochemical characterization of the morphologically identified natural hybrid Solidago×niederederi Khek compared with the native Solidago virgaurea and two invasive species, Canada goldenrod ( Solidago canadensis L.) and giant goldenrod ( Solidago gigantea Aiton). The phenolic compounds, namely, chlorogenic acid, rutin, isoquercitrin, hyperoside, and quercitrin, were detected in leaves and inflorescences by the high-performance liquid chromatography–photodiode array detector/ultraviolet (PAD/UV) method. All analyzed Solidago species contained all of the phenolic compounds investigated. The quantitative phytochemical differentiation among Solidago taxa was shown by principal component analysis. The results indicated that S. gigantea plants were characterized by significantly different quantities of phenolic compounds compared with three other Solidago taxa, which formed a separate cluster in the space of the principal component model, indicating the high similarity of their profiles. An additional multivariate analysis of the three species studied revealed a chemical gradient from S. canadensis to S. virgaurea with a slightly overlapping zone on the score plots presented by S.×niederederi and S. virgaurea accessions. The results showed that S.×niederederi was closely related to S. virgaurea. This result is suggestive of a hybrid origin with significant contributions from the native species. However, S.×niederederi was significantly different from its parental species with respect to chlorogenic acid and quercitrin in leaves and rutin with isoquercitrin in inflorescences. Conversely, samples indicating intermediate chemical composition between native S. virgaurea and invasive S. gigantea were not distinguished. The comparison of phenolic compound accumulation in Solidago plants supported the additional identification of the origin of S.×niederederi .